Άριστες νομισματικές επιλογές: η ελληνική περίπτωση κατά την περίοδο 1988-1995 - Απέργης, Νικόλαος Ε.; Αστερίου, Δημήτριος (SPOUDAI Journal of Economics and Business, 1998)
It has been nearly 25 years since Poole (1970) in his classic paper on the issue of optimal choice of the monetary policy instrument in a stochastic IS-LM model argued that the Monetary Authorities (MA) can control either the interest rate or the money supply (or reserve base money). The basic hypothesis of this paper within the neoclassical school of thought is that the MA desire to control the stock of money, which is the most important factor that determines the behavior of the price level. This paper employs an econometric model to examine the optimal choice of the monetary instrument for the case of the Greek economy over the period 1988-1995. The empirical results provide evidence in favor of the MA's current choice of using the interest rate as the primary monetary instrument.